Criteria For Forming Professional Qualities Of Future Technological Education Teachers - Xaliqulov E. (Euro Asian Journal Publishing, 2024)
This article describes in detail the criteria, methods, features and professionalskills of the formation of professional qualities of future teachers of technological education in the education system.
Keywords: professional quality; skill; education; psychological